2010
DOI: 10.1111/j.1475-2743.2010.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

The need for harmonizing methodologies for assessing soil threats in Europe

Abstract: Central to the EU thematic strategy for soil protection is that areas affected by soil degradation through erosion, soil organic matter decline, compaction, salinization and landslides should be identified in a clear and consistent way. However, the current methodologies to achieve this often differ and this can result in different perceptions of risks among EU Member States. The aims of this paper are to i) assess the current status of assessment methodologies in Europe (EU27) associated with erosion, soil or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This understanding as such is not new. For instance, in Hungary, the depth of the groundwater level is a major factor in assessing the risk of root zone salinity and sodicity [ Szabolcs , 1989; Toth , 2008; Toth and Szendrei , 2006; Van Beek et al , 2010; Varrallyay , 1989]. The awareness that salts need to be leached to avoid soil salinity is expressed in the concept of leaching fraction as given in the famous work by Richards et al [1954].…”
Section: Introductionmentioning
confidence: 99%
“…This understanding as such is not new. For instance, in Hungary, the depth of the groundwater level is a major factor in assessing the risk of root zone salinity and sodicity [ Szabolcs , 1989; Toth , 2008; Toth and Szendrei , 2006; Van Beek et al , 2010; Varrallyay , 1989]. The awareness that salts need to be leached to avoid soil salinity is expressed in the concept of leaching fraction as given in the famous work by Richards et al [1954].…”
Section: Introductionmentioning
confidence: 99%
“…The definition of risk‐based priority areas requires quantitative estimation of risk from erosion by water. Van Beek et al. (2010) identified several models in use for estimating soil loss by rill, inter‐rill and sheet erosion, which were mainly modifications of the well‐established Universal Soil Loss Equation (Wischmeir & Smith, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The definition of risk-based priority areas requires quantitative estimation of risk from erosion by water. Van Beek et al (2010) identified several models in use for estimating soil loss by rill, inter-rill and sheet erosion, which were mainly modifications of the well-established Universal Soil Loss Equation (Wischmeir & Smith, 1978). The ENVASSO project also evaluated soil threat models and selected the PESERA model (Kirby et al, 2004) for quantitative estimation of soil loss by rill, inter-rill and sheet erosion.…”
Section: Estimation Of Soil Degradation and Its Effect On Soil Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For developing the evaluation functions many data is required, which is a major challenge (Wienhold et al, 2009). Also, when collecting data, it is important that data are collected and analysed using the same methods, to allow comparison of data (Van Beek et al, 2010). Currently many VSEs have been collected worldwide (e.g.…”
Section: Development Of Universal Visual Soil Evaluationsmentioning
confidence: 99%